Enhancement of the Properties of Compressed Stabilized Earth Blocks through the Replacement of Clay and Silt with Fly Ash - Malkanthi, S. N.; Perera, A. A. D. A. J.; Galabada, G. H.; Dharmaratne, P. D. (Engineering, Technology & Applied Science Research, 2021)
The use of earth as a building material, in different forms, such as unburnt and burnt bricks, rammed earth, mud blocks, and soil blocks, is a common practice globally. This study is focused on soil blocks stabilized with cement which are referred to as Cement Stabilized Earth Blocks (CSEBs). The strength and durability of CSEBs are primarily governed by the amount of silt and clay content (finer) in the soil. Many researchers have shown that low finer content improves the properties of CSEB and they have altered the finer content by adding different additives. The current study used a washing method to reduce the finer content and fly ash was utilized as finer to re-fill the soil to the required finer content amount. Also, soil grading was modified by adding larger particles that were separated from the same soil to fit the soil grading to the optimization curves mentioned in the literature. The finer content was changed to 5%, 7.5%, and 10%. Blocks were made by stabilizing the soil with 6%, 8%, and 10% cement and with the size of 150mm×150mm×150mm. The results revealed that fly ash addition up to 10% improves the properties of CSEBs and compressive strength changes from 4.28N/mm2 to 13.43N/mm2.